Effect of Variation in Pineapple Leaf Fiber Composition with Polyurethane Matrix in Composite Panels on Acoustic Properties and Porosity - Putra Adil; Yenni Darvina; - Ramli; Rio Anshari (PILLAR OF PHYSICS, 2023)
Noise can cause medical, psychological, and environmental disturbances. One of the efforts to reduce noise is by using acoustic materials. Acoustic materials can be made using natural fiber composites. This study uses pineapple leaf fiber as fiber and polyurethane as a matrix that will be formed into a sound-absorbing composite panel. This study aims are to determine the effect of variations in the composition of pineapple fiber-reinforced composites with polyurethane matrix on acoustic properties and porosity, determine the effect of frequency on acoustic properties, and determine the relationship between porosity and acoustic properties. The method used in this research uses a characterization tool in the form of a one-microphone impedance tube and porosity test equipment. Composite panels are made by varying the composition of pineapple leaf fibers with polyurethane matrix with the ratio of pineapple leaf fiber composition to polyurethane matrix, namely 50%: 50%, 60%: 40%, 70%: 30%, 80%: 20% and 90%: 10%. Based on the research, it was  found that the more the amount of pineapple leaf fiber composition is used, the absorption coefficient, sound transmission loss, and prostitution will increase while the reflection coefficient decreases. The higher the frequency used, the absorption coefficient and sound transmission loss will increase while the reflection coefficient decreases for all frequencies. The relationship between porosity and acoustic properties is that the higher the porosity, the absorption coefficient and sound transmission loss will increase while the reflection coefficient decreases